Path Planning for Rapid DEDAM Processing Subject to Interpass Temperature Constraints - Glenn W. Hatala; Edward W. Reutzel; Qian Wang (Metals)
Directed energy deposition (DED) additive manufacturing (AM) enables the production of components at a high deposition rate. For certain alloys, interpass temperature requirements are imposed to control heat accumulation and microstructure transformation, as well as to minimize distortion under varying thermal conditions. A typical strategy to comply with interpass temperature constraints is to increase the interpass dwell time, which can lead to an increase in the total deposition time. This study aims to develop an optimized tool path that ensures interpass temperature compliance and reduces overall deposition time relative to the conventional sequential deposition path during the DED process. To evaluate this, a compact analytic thermal model is used to predict the thermal history during laser-based directed energy deposition (DED-LB/M) hot wire (lateral feeding) of ER100S-G, a welding wire equivalent to high yield steel. A greedy algorithm, integrated with the thermal model, identifies a tool path order that ensures compliance with the interpass requirement of the material while minimizing interpass dwell time and, thus, the total deposition time. The proposed path planning algorithm is validated experimentally with in situ temperature measurements comparing parts fabricated with the baseline (sequential) deposition path to the modified path (resulting from the greedy algorithm). The experimental results of this study demonstrate that the proposed path planning algorithm can reduce the deposition time by 9.2% for parts of dimensions 66 mm × 73 mm × 16.5 mm, comprising 15 layers and a total of 300 beads. Predictions based on the proposed path planning algorithm indicate that additional reductions in deposition time can be achieved for larger parts. Specifically, increasing the (experimentally validated) part dimension perpendicular to the deposition direction by five-times is expected to result in a 40% reduction in deposition time.